2021
DOI: 10.2147/jmdh.s306959
|View full text |Cite
|
Sign up to set email alerts
|

Turnover Intention and Its Associated Factors Among Health Extension Workers in Illubabora Zone, South West Ethiopia

Abstract: Background The efficiency and quality of a health service can be compromised by turnover intention. Employees who intend to leave their job may identify themselves in the form of withdrawal, being predisposed to lateness, absenteeism, and declining participation. This study aimed to determine the level of turnover intention and to identify factors associated with turnover intention among health extension workers in the Illubabora zone. Methods A facility-based cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Besides the time and energy, it poses greater dissatisfaction and misery in their life. This finding is consistent with a study conducted in Illubabora Zone; South West Ethiopia suggested that providing transportation is another important mechanism to reduce the workload [ 30 ]. Similar finding was observed in other studies in which 41% of HEWs’ was spent on travel in 2014 study [ 17 ] and a study in 2017, out of the total observed work time, HEWs spent 16% of their time through travel between work activities [ 25 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Besides the time and energy, it poses greater dissatisfaction and misery in their life. This finding is consistent with a study conducted in Illubabora Zone; South West Ethiopia suggested that providing transportation is another important mechanism to reduce the workload [ 30 ]. Similar finding was observed in other studies in which 41% of HEWs’ was spent on travel in 2014 study [ 17 ] and a study in 2017, out of the total observed work time, HEWs spent 16% of their time through travel between work activities [ 25 ].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the magnitude of HEWs ' intention to leave their current position was high due to a heavy workload, a lack of enthusiasm, and a limited career structure, which were all significant predictors of turnover intention. [ 30 ]. Workload, large distances, and a lack of support were all highlighted as problems that could demotivate HEWs from providing outreach services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 29 included studies, 9 were from Amhara,16–24 8 were from Oromia,25–32 3 were from Addis Ababa,33–35 2 studies each from Tigray,36 37 Sidama,13 38 multiregional12 39 and Nationwide40 41 and one study was from Gambella 42. The study from Sidama region13 documented the highest prevalence (83.7%) of turnover intention among health professionals, while the lowest prevalence (39%) was documented from a study conducted by including the three regions of Afar, Gambela and Benishangul Gumz 12.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies included a mixed variety of health professionals in general,13 17–19 25 27 28 30 32 34 35 42 while 10 other studies included nurse professionals only 20 22 23 26 31 33 36–38 40. Two studies included health extension workers16 29 and five studies each included physicians,39 health information technology professionals,24 anaesthetists,41 medical laboratory professionals21 and midwives,12 respectively. Table 1 summarises the characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%